Pengaruh Rekrutmen Pegawai, Komitmen Organisasi Dan Motivasi Kerja Terhadap Kinerja Pegawai Di Dinas Komunikasi Dan Informatika Kota Surabaya - Bayurukmawati, Indri; Sedarmayanti (Soetomo Magister Ilmu Administrasi, 2024)
Research entitled The Effect of Employee Recruitment, Organizational Commitment and Work Motivation on Employee Performance in the Communication and Information Service of the City of Surabaya is a study that analyzes employee performance that is influenced by. Employee Recruitment, Organizational Commitment and Work Motivation at the Surabaya City Communication and Informatics Service. Current conditions show an increase or decrease in the performance of employees of a company or organization in an effort to achieve its goals influenced by the employee recruitment process, organizational commitment and employee motivation. It can be concluded that sequentially the process of achieving performance begins with recruiting employees through selection to training tailored to the needs of the company or organization. This recruitment process is followed by the distribution of work by company management which is supported by the commitment of employees to dedicate themselves to their performance to achieve the expected goals. The employee’s commitment will lead to motivation according to the character of each employee which is an encouragement to contribute to the success of company or organization goals. Researchers use a quantitative type research approach Quantitative research is a research method based on the philosophy of positivism that is used to examine samples from certain populations with the aim of testing the hypotheses that have been set. The population in this study were all employees who worked at the Surabaya City Communication and Informatics Office, with a total of 215 employees consisting of 36 employees with PNS status and 179 status as honorary or non-PNS employees. The sample used was 100 people.